(untitled) (Revista Brasileira de Contabilidade e Gestão, 2013)
The third sector is characterized by aid to areas in need where the government is distant or unable to provide adequate support. They are societies of persons constituted by means of associations or foundations. Due to their social objective they have unique accounting and tax aspects. In view of this information, we question the usefulness of accounting in these organizations. Due to the time of existence of the Association of Volunteer Firefighters of Presidente Getúlio, developing this study in this entity was decided, with the main objective of identifying its most relevant managerial and accounting aspects. Thus, we developed a descriptive study, from the techniques of bibliographic research and case study with qualitative data analysis. From the information provided by the association and its accounting, we elaborated graphs showing the inputs, outputs and income of the association for the period of 2011, March to November 2012, as well as a graph based on the voluntary hours of 2013 highlighting the value of human resources. By analyzing the documents, deficiencies and suggestions for improvement were pointed out to the entity, aiming at its evolution. In conclusion, the entity has as higher revenue and simultaneously cost, the voluntary labor, a relevant factor that, among others, could be highlighted in accounting tools such as the social balance sheet.